MENINGKATKAN KINERJA BISNIS MELALUI KOMPETENSI SOSIAL DAN RELASIONAL JEJARING ENTREPRENEUR - Ahmad Sidiq; Handayani Tri Wijayanti (Universitas Muhammadiyah Semarang, 2017)
The behavior of entrepreneurs in doing business and interacting with stakeholders leads to the inherent social competence in them. Social competence becomes the foundation of the relational formation of SME business networks that will help SMEs in interacting with external parties. Relational networking entrepreneurs will open business opportunities for SMEs so that the impact on business development, survival, and growth of the firm. This study contributes to entrepreneurship theory by examining the influence of social competence and relational network of entrepreneurs on the performance of SMEs. Convenience sampling method is used to collect primary data. A sample of 103 SMEs in Surakarta was used for multiple regression analysis in hypothesis testing in this study. The research findings were successful in verifying the influence of social competence and relational of entrepreneur network on business performance. Relational networks of entrepreneurs become the central point that would mediate the relationship between social competence which is owned by an entrepreneur in improvingbusiness performance. Social competence makes entrepreneurs active in conducting business interactions and extending network relational with various parties so that specific information will be collected to assist companies in achieving the goal of superior business performance. Keywords : Social Competence, Network Relational, Business Performance